ANALYSIS OF FACTORS INFLUENCING INTERNATIONAL STUDENTS' SATISFACTION IN HIGHER EDUCATION - Nurrahma, Yashinta; Rosalinda, Gigih Devy; Kurniawati, Desy (Jurnal Administrasi Pendidikan, 2024)
This research aims to analyze whether there is a significant relationship between the variables of Teacher Expertise, Courses Offered, Learning Environment, and Facilities toward the satisfaction of international students in the Non-Degree and Full Degree programs at University X. The research sample consisted of 92 international students, and data collection was conducted through an online questionnaire poll. The research methodology used was the Partial Least Square (PLS) statistical technique, which includes two stages: Outer Model Analysis and Inner Model Analysis. The research findings indicate that the key factors significantly influencing the satisfaction of non-degree program students are the expertise of the teachers and the courses offered, with the latter being the most influential factor. Conversely, for Full-Degree program students, the only factor that significantly affects their satisfaction is the variable of the learning environment. The variables of teaching expertise and courses offered in the non-degree program show a significant relationship with student satisfaction, as they have p-values 0.05 and T-statistics 1.96. The p-values for teaching expertise and courses offered are 0.032 and 0.008, respectively, and the T-statistics are 2.776 and 2.212, respectively. On the other hand, in the Full Degree program, only the variable of Learning Environment shows a significant relationship with student satisfaction, with a p-value of 0.013 and a T-statistic of 2.581. The research highlights the need to strengthen teaching quality and enhance campus facilities for both Full Degree and Non-Degree programs. It is expected that these improvements will increase the enrollment of international students in the future.